Phytochemical analysis and antioxidant activity of some thymus species from Romania - Florina Căpățină; Eva Suciu; Daniela Benedec (Amaltea Medical Publishing House, 2021)
Objectives. Thymus species, T. vulgaris, T. serpyllum, T. comosus and T. glabrescens, are medicinal plants from the spontaneous Romanian flora used for their antibacterial, antispasmodic, expectorant, anti-inflammatory, anthelmintic properties, especially the plant products obtained from T. vulgaris. The aim of this study was to comparatively investigate the polyphenolic composition, as well as the in vitro antioxidant activity of some ethanolic extracts obtained from the aerial parts of thymus sp. Materials and methods. The polyphenols, flavonoids, phenolic acids and tannins contents in the four samples thymus sp. ethanolic extracts were spectrophotometrically determined. The identification of the most important polyphenolic compounds was performed by the method of thin layer chromatography method (TLC). The antioxidant activity of hydroalcoholic extracts was evaluated in vitro by the DPPH method. Outcomes. Following the analyzes performed, it can be revealed that there are both qualitative and quantitative differences in the polyphenolic composition of the four species of thyme studied, the richest in active principles being T. vulgaris and T. serpyllum. Conclusions. In this paper it has been shown that thyme species are medicinal plants rich in antioxidant polyphenolic active principles, and their use for the treatment of certain diseases can be justified. In addition to the officinal species: T. vulgaris, T. serpyllum, other thyme species from the spontaneous flora of our country can be used in phytotherapy, such as: T. comosus, T. glabrescens.